Mobilization of lymphatic endothelial precursor cells and lymphatic neovascularization in primary Sjögren's syndrome. Issue 4 (1st February 2016) - Alunno, Alessia; Ibba‐Manneschi, Lidia; Bistoni, Onelia; Rosa, Irene; Caterbi, Sara; Gerli, Roberto; Manetti, Mirko
Abstract: Although lymphatic neovascularization may be a key feature of chronic inflammation, it is almost unexplored in primary Sjögren's syndrome (pSS). A recent study revealed a pro‐lymphangiogenic function of interleukin (IL)‐17, a leading player in pSS pathogenesis. The aims of the study were to investigate lymphangiogenic mediators and lymphatic vasculature in pSS, as well as their possible association with IL‐17. Circulating lymphatic endothelial precursor cells (LEPCs) and Th17 cells were enumerated in pSS patients and healthy donors. VEGF‐C and IL‐17 levels were assessed in paired serum samples. Lymphatic vasculature, VEGF‐C/VEGF receptor (VEGFR)‐3 and IL‐17 were evaluated in pSS minor salivary glands (MSGs) and compared with normal and non‐specific chronic sialadenitis (NSCS) MSGs. Circulating LEPCs were expanded in pSS and correlated with circulating Th17 cells, IL‐17 and VEGF‐C. In pSS MSGs, a newly formed lymphatic capillary network was found within periductal inflammatory infiltrates and the number of interlobular lymphatic vessels was significantly increased compared with normal and NSCS MSGs. Strong VEGF‐C expression was detected in pSS ductal epithelial cells and periductal inflammatory cells. Numerous VEGFR‐3 + infiltrating mononuclear cells were exclusively observed in pSS MSGs. VEGFR‐3 expression was strongly increased in lymphatic capillaries of pSS MSGs. IL‐17 + inflammatory cells were preferentially observed around lymphatic vessels in pSS MSGs. This study supports the notion that lymphvasculogenesis and lymphangiogenesis are active in pSS, thereby unmasking a novel aspect of disease pathogenesis. In addition, our results suggest another possible pathogenic role of IL‐17 in pSS, further supporting its therapeutic targeting in this disease.